Thai Supplementary Development on the Title of Thai Grammatical in Thai Curriculum for Mathayomsuksa 2 - Jonglakha, Weerasak; Bunyaboon, Anothai; Yimcharoenpornsakul, Narongrid; Kodsongkram, Supaporn; Aukarapisit , Supparat; Rianpreecha, Chompoonut (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: This study aims: (1) to create and to find the proficiency. And (2) to compare the proficiency with the pretest and posttest on Thai supplementary development on the title of Thai Grammatical in Thai Curriculum for Mathayomsuksa 2 students, the semester 1 of the academic year of 2566. The 27 populations, randomized by purposive sampling for 1 classroom, were Mathayomsuksa 2 students, the semester 1 of an academic year of 2566. Methodology: The instruments were 10 sets of Thai supplementary development on the title of Thai Grammatical in Thai Curriculum for Mathayomsuksa 2 students, the 40 items with Multiple Choice on achievement test. The statistical procedures employed to examine the data were Percentage, Mean, and Standard Deviation. Results: The results of the study were the following: (1) Teaching set on principles of language use Thai language learning group For Mathayomsuksa 2 students, the efficiency was 84.19/82.40, higher than the set criteria. And (2) Thai supplementary development on the title of Thai Grammatical in Thai Curriculum for Mathayomsuksa 2 was statistically significantly different at level 0.01, accepted the hypothesis determination. Conclusion: The study exceeded predetermined standards for Mathayomsuksa 2 students and showed the efficacy of teaching strategies based on language principles. Furthermore, the study's hypotheses are supported by the noteworthy enhancement in Thai grammatical understanding, which is supported by statistical significance at the 0.01 level. This validates the effectiveness of Thai supplementary development within the curriculum.